The Power of the Street: Evidence from Egypt’s Arab Spring - Acemoglu, Daron; Hassan, Tarek A.; Tahoun, Ahmed (Review of Financial Studies, 2018)
Unprecedented street protests brought down Mubarak's government and ushered in an era of competition between three rival political groups in Egypt. Using daily variation in the number of protesters, we document that more intense protests are associated with lower stock market valuations for firms connected to the group currently in power relative to non-connected firms, but have no impact on the relative valuations of firms connected to rival groups. These results suggest that street protests serve as a partial check on political rent-seeking. General discontent expressed on Twitter predicts protests but has no direct effect on valuations.